2022
DOI: 10.48550/arxiv.2202.09820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chimeric forecasting: combining probabilistic predictions from computational models and human judgment

Abstract: Forecasts of the trajectory of an infectious agent can help guide public health decision making. A traditional approach to forecasting fits a computational model to structured data and generates a predictive distribution. However, human judgment has access to the same data as computational models plus experience, intuition, and subjective data. We propose a chimeric ensemble-a combination of computational and human judgment forecasts-as a novel approach to predicting the trajectory of an infectious agent. Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As demonstrated during previous infectious disease outbreaks, crowdsourced human judgment can successfully estimate many different quantities that have epidemiological meaning or are of importance to public health decision makers. [3][4][5][6][7][8] During the 2014-15 and 2015-16 influenza seasons, crowdsourced forecasts of influenza-like illness were collected and found to be among the most accurate when compared to computational forecasts. 3 Beginning on Feb 18, 2020, just before WHO declared COVID-19 a pandemic, experts in infectious disease modelling were called upon to generate predictions of a diverse set of quantities related to COVID-19, including the number of weekly incident cases at the US national level, the cumulative number of deaths by the end of 2020, and counterfactual values (eg, the reported number of cases at the state level under two different potential policy changes).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated during previous infectious disease outbreaks, crowdsourced human judgment can successfully estimate many different quantities that have epidemiological meaning or are of importance to public health decision makers. [3][4][5][6][7][8] During the 2014-15 and 2015-16 influenza seasons, crowdsourced forecasts of influenza-like illness were collected and found to be among the most accurate when compared to computational forecasts. 3 Beginning on Feb 18, 2020, just before WHO declared COVID-19 a pandemic, experts in infectious disease modelling were called upon to generate predictions of a diverse set of quantities related to COVID-19, including the number of weekly incident cases at the US national level, the cumulative number of deaths by the end of 2020, and counterfactual values (eg, the reported number of cases at the state level under two different potential policy changes).…”
mentioning
confidence: 99%
“…5 Additional studies have found that human judgment and computational modelling might complement one another. [6][7][8] We collected 686 unique and revised predictions (358 unique and 328 revised) from May 19 to May 24, 2022, on the Metaculus human judgment crowd sourcing platform (methods, limitations, and TRIPOD reporting guidelines are in the appendix pp 15-19).…”
mentioning
confidence: 99%
“…A more detailed review of techniques prior to COVID-19 can be found in [15]. During the COVID-19 pandemic, this crowd-sourced approach has been used to evaluate vaccine policies [16] and combined with computational models to produce hybrid/ensemble forecasts [17, 18]. Recently, for the emerging monkeypox outbreak, human judgment forecasts were used to estimate cases, deaths, and impact across Europe, US and Canada [19].…”
mentioning
confidence: 99%